Pancreatic Cancer Following Acute Pancreatitis: A Population-based Matched Cohort Study. (November 2018) - Sadr-Azodi, Omid; Oskarsson, Viktor; Discacciati, Andrea; Videhult, Per; Askling, Johan; Ekbom, Anders
Abstract Background Acute pancreatitis is linked to pancreatic cancer, but the direction of this association is not fully elaborated. Methods This was a population-based cohort study including all Swedish residents diagnosed with a first-time episode of acute pancreatitis between 1997 and 2013 and corresponding matched pancreatitis-free individuals from the general population. Hazard ratios for the association between acute pancreatitis and pancreatic cancer were estimated using multivariable Cox regression models. Results Overall, 49, 749 individuals with acute pancreatitis and 138, 750 matched individuals without acute pancreatitis were followed up for 1, 192, 134 person-years (median 5.3 years). A total of 769 individuals developed pancreatic cancer, of whom 536 (69.7%) had a history of acute pancreatitis. The risk of pancreatic cancer was substantially increased during the first few years after a diagnosis of acute pancreatitis but declined gradually over time, reaching a level comparable to the pancreatitis-free population after >10 years of follow-up. In those with non-gallstone-related acute pancreatitis, the risk of pancreatic cancer declined to a level comparable to the pancreatitis-free population only when follow-up time was censored for a second episode of acute pancreatitis or a diagnosis of chronic pancreatitis. Increasing number of recurrent episodes of acute pancreatitis was associated with increased risk of pancreatic cancer. Conclusion These findings imply a delay in the diagnosis of pre-existing pancreatic cancer, if clinically presented as acute pancreatitis. Any association between non-gallstone-related acute pancreatitis and pancreatic cancer in the long-term (>10 years) could be mediated through recurrent acute pancreatitis or chronic pancreatitis.